Surveilens Epidemiologi HIV/AIDS di Rumah Sakit Pemerintah di Jakarta Selatan pada 2005 - AGUS PURWANGGANA; ENDANG POEDJININGSIH; MUNIRO MUNIRO (Fakultas Farmasi Universitas Pancasila, 2009)
HIV/AIDS has become a pandemic disease Which hits the Whole World including Indonesia. Antiretroviral (ARV) drugs are drugs pursuing HIV replication. A Government Hospital in South Jakarta is among hospitals that accept training on Voluntary Counseling and Testing (VCT) by the Department of Health, Republic of Indonesia, and has been a reference hospital for the medication of HIV/AIDS and its associated opportunistic infection in people With HIV/AIDS. This epidemiologic surveillance was conducted to find out proportion number, Case Fatality Rate (CFR), incidence rate and prevalence rate of all incidents related to HIV/AIDS. Data collection for people with HIV/AIDS was done through drug counseling cards, medical records and the laboratory examination results, and data analysis Was performed using Stata 7.0 software. Antiretroviral diugs often used in the Government Hospital in South Jakarta were Duviral-Neviral, Duviral-Evafir and Hiviral-Stavudin-Evahr. The results of this study show that the goals of the surveilance conducted can be achieved except for the number of incidence. Among 397 patients suspected to have HIV/AIDS, 324 patients had risk factor of HIV/AIDS, 240 patients were diagnosed positive HIV 290 patients Were severed with opportunistic infections, and 104 patients died.